THE INFLUENCE OF AUDITOR ETHICS ON AUDIT QUALITY IN PINRANG DISTRICT INSPECTORATE OFFICE - Sarmila S; Rismala; Indrayani (Institut Agama Islam Negeri Parepare, 2024)
Audit quality is defined as the probability of an Auditor determining and reporting fraud that occurs in the client's accounting system. The higher the audit quality produced by the auditor, the higher the confidence of information users in using financial reports. This research aims to determine the influence of auditor ethics on audit quality at inspectorate offices. This type of research is quantitative research in the form of a questionnaire with uses an exploratory approach using data collection techniques, namely primary in the form of questionnaires and secondary data obtained indirectly which is tested using descriptive statistical analysis tests, validity tests, reliability tests, classical assumption tests, hypothesis tests. The results of this research show that: (1) Auditor integrity partially influences audit quality, this is proven by a significant value of 0.033, which is <0.05. (2) Objectivity partially influences audit quality, this is proven by a significant value of 0.000 where <0.05. (3) Partial competency has no effect on audit quality, this is proven by a significant value of 0.449, which is > 0.05. (4) Auditor confidentiality does not partially influence audit quality, this is proven by a significant value of 0.179, which is > 0.05. (5) The auditor's professional behavior partially influences audit quality, this is proven by a significant value of 0.000, where <0.05. Integrity (X1), Objectivity (X2), Competence (X3), Creativity (X4) and Professional Behavior (X5) simultaneously influence audit quality, this is proven by the F valuecount 47,563 > Ftable2.53 and a significant value of 0.000 <0.05.